2003
DOI: 10.1107/s0907444903018493
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an insect δ-class glutathioneS-transferase from a DDT-resistant strain of the malaria vectorAnopheles gambiae

Abstract: Glutathione S-transferases (GSTs) are a major family of detoxification enzymes which possess a wide range of substrate specificities. Most organisms possess many GSTs belonging to multiple classes. Interest in GSTs in insects is focused on their role in insecticide resistance; many resistant insects have elevated levels of GST activity. In the malaria vector Anopheles gambiae, elevated GST levels are associated with resistance to the organochlorine insecticide DDT [1,1,1-trichloro-2,2-bis-(p-chlorophenyl)ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…However, the advent of DDT resistant strains of mosquitoes has decreased the effectiveness of this control measure [11]. A DDT resistant strain of A. gambiae has been found to have elevated levels of multiple epsilon class GSTs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the advent of DDT resistant strains of mosquitoes has decreased the effectiveness of this control measure [11]. A DDT resistant strain of A. gambiae has been found to have elevated levels of multiple epsilon class GSTs.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated GST activity has been detected in strains of insects that are resistant to organophosphates and organochlorines [4,9]. Insect GSTs have been classified into six classes: d, 1, s, u, v, and j [11]. The d and 1-class GSTs have been associated with detoxification of various insecticides [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because GST genes play important roles in detoxification pathways and the oxidative stress response, studies on GST resistance have been widely reported in insects, including Drosophila melanogaster Low et al 2007;Sawicki et al 2003;Tang and Tu 1994;Tu and Akgul 2005), Anopheles gambiae (Chen et al 2003;Ding et al 2003Ding et al , 2005Ranson et al 2000Ranson et al , 2001, and Bombyx mori (Yamamoto et al 2006;Yu et al 2008), but information about other important species is rather limited. Honey bees, which serve as an excellent model for social behavior research, are a major plant pollinator and thus play essential roles in agriculture and ecological balance.…”
Section: Introductionmentioning
confidence: 99%